Comparing features in metallurgical interaction when applying different techniques of arc and plasma surfacing of steel wire on titanium - Korzhyk, Volodymyr; Khaskin, Vladyslav; Grynyuk, Andrii; Ganushchak, Oleg; Peleshenko, Sviatoslav; Konoreva, Oksana; Demianov, Oleksii; Shcheretskiy, Volodymyr; Fialko, Nataliia (Eastern-European Journal of Enterprise Technologies, 2021)
This paper reports a study into the regularities of interphase interaction, features in the formation of intermetallic phases (IMPs), and defects when surfacing steel on titanium in four ways: P-MAG, CMT, plasma surfacing by an indirect arc with conductive wire, and PAW. A general tendency has been established in the IMP occurrence when surfacing steel on titanium by all the considered methods. It was determined that the plasma surfacing technique involving an indirect arc with conductive wire is less critical as regards the IMP formation. That makes it possible to obtain an intermetallic layer of the minimum thickness (25...54 μm) in combination with the best quality in the formation of surfaced metal beads. Further minimization of the size of this layer is complicated by a critical decrease in the heat input into the metal, which gives rise to the capability of the surfaced metal to be collected in separate droplets. The formation of TiFe2, TiFe, and the α-Fe phase enriched with titanium in different percentage compositions has been observed in the transition zone of steel surfacing on titanium under different techniques and modes of surfacing. The study has shown the possibility of formation, in addition to the phases of TiFe2 and TiFe, the Ti2Fe phase at low heat input. The technique of plasma surfacing by an indirect arc with conductive wire minimizes the thermal effect on the base metal. When it is used at the border of the transition of the layer of steel surfaced on titanium, the phase composition and structure of the layers in some cases approach the composition and structure of the transition zone of the original bimetallic sheet "titanium-steel" manufactured by rolling. A layer up to 5 μm thick is formed from the β phase with an iron concentration of 44.65 % by weight and an intermetallic layer up to 0.2...0.4 μm thick, close in composition to the TiFe phase. The next step in minimizing the IMP formation might involve the introduction of a barrier layer between titanium and steel.